Wave scattering from non-Gaussian rough surfaces at terahertz frequencies - Alissa, Mai; Sheikh, Fawad; Abbas, Ali Al Haj; Kaiser, Thomas (2019 2nd International Workshop on Mobile Terahertz Systems, IWMTS 2019, 2019)
Concerning the facile solution to the problem of electromagnetic waves' scattering by a random rough surface, the surface distribution is generally assumed to be Gaussian. In this work, the scattering by non-Gaussian rough surfaces is investigated analytically and by simulation at terahertz (THz) frequencies. We found that for a slightly rough surface, a change in the distribution plays no major role in the scattering behavior at frequency of interest. However, for a very rough surface, with standard height deviations in the order of wavelength, the scattering pattern was distinctly affected thus changing the distribution when all other scattering factors are constant. The simulation results agree well with the analytical model, and prove that a normally distributed surface model may exhibit as an overly general surface to all random rough surfaces at THz frequencies.
Created from Fastlane, Scopus look-up
Keywords: Non-Gaussian rough surfaces; Probability density function; Scattering model; Terahertz communications